2018
DOI: 10.1159/000495635
|View full text |Cite|
|
Sign up to set email alerts
|

The Kidney Specific Protein myo-Inositol Oxygenase, a Potential Biomarker for Diabetic Nephropathy

Abstract: Background/Aims: Renal tubular injury plays an important role in the progression of diabetic nephropathy (DN). However, there is a lack of specific biomarkers for tubular damage in incipient DN. We have evaluated the role of myo-inositol oxygenase (MIOX) in the tubular injury of DN, but whether it could serve as a new biomarker for the early diagnosis of DN is unclear. Methods: Ninety patients with type 2 diabetes mellitus (T2DM) were divided into normoalbuminuria, microalbuminuria and macroalbuminuria groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, it has been clinically found that diabetes, sepsis and ischemia/reperfusion increase sensitivity to AKI 43 45 . Miox expression significantly increased in patients with type 2 diabetes mellitus and correlated with tubulointerstitial lesiony 27 . Importantly, in diabetic patients without early signs of glomerular damage, serum and urine MIOX levels have increased.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, it has been clinically found that diabetes, sepsis and ischemia/reperfusion increase sensitivity to AKI 43 45 . Miox expression significantly increased in patients with type 2 diabetes mellitus and correlated with tubulointerstitial lesiony 27 . Importantly, in diabetic patients without early signs of glomerular damage, serum and urine MIOX levels have increased.…”
Section: Discussionmentioning
confidence: 95%
“…Urinary myo-inositol and Miox tissue expression were associated with the initial estimated GFR in focal segmental glomerulosclerosis patients 24 . Recent studies further found that Miox is a kidney-specific proximal tubule protein that increased in the serum of animal with AKI or diabetic nephropathy and the plasma of patients with severe AKI patients or type 2 diabetes mellitus 25 27 . In addition, cadmium-induced toxicity in mice kidney significantly increased Miox levels in the tubular cells 28 , and the Miox concentration in the serum and urine may negatively reflect the rental function 29 .…”
Section: Introductionmentioning
confidence: 98%
“…In determining biomarkers with most potential in DKD, several factors require consideration, one involves the way participants are categorised within cross‐sectional studies. Most studies have stratified participants into stages of albuminuria as markers of DKD, namely, microalbuminuria and/or macroalbuminuria 40–42,44,51–57,59,63,64,105,106,108–111,113–116,119–124,127,129,130 . However, the use of albuminuria is contentious given that progression in the albuminuric stage is not a necessary prerequisite for the development of DKD 4,14 .…”
Section: Discussionmentioning
confidence: 99%
“…This emphasises the inaccuracies that exist with eGFR as a marker of kidney function. 133 Other kidney injury biomarkers that were investigated in crosssectional studies but infrequently cited include, urine megalin, uromodulin, immunoglobulins, netrin-1, cyclophilin-A, myo-inositol oxygenase and glypican-5 107,114,119,[126][127][128][129][130][131] (Table 6). Further research would assist with validation of these markers.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation